OBSERVATIONS OF TYPICAL, RARE AND UNIQUE PHENOMENA IN CLOSE BINARIES WITH EXTREMAL MASS RATIO - Kuznetsova, Yu. G.; Pavlenko, E. P.; Sharipova, L. M.; Shugarov, S. Yu. (Одеські астрономічні публікації, 2017)
We present the review of different properties of several close binary systems, based on our observations. These binaries are as follow: SU UMa type stars V503 Cyg and V1504 Cyg, X-Ray novae V518 Per and V404 Cyg. They have the extremal mass ratio of the primary component to the secondary M1/M2 > 3. Some of them show the typical for the SU UMa type stars behaviour, so-called the "positive superhumps" or more rare "negative superhumps". Another display the "forbidden" variability in the ordinary outbursts or the light variation of unknown yet nature.